2012
DOI: 10.1039/c2sm07223h
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of block copolymers composed of charged and neutral blocks

Abstract: This article reviews current experimental observations and theoretical calculations devoted towards understanding micro-phase separation in charged block copolymer systems. We discuss bulk morphologies in melt and in solution, as well as some of the new emerging research directions. Overall, a comprehensive picture is beginning to emerge on the fundamental role of electrostatics in the microphase separation of charged block copolymers. This understanding provides exciting new insight that may be used to direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 172 publications
(295 reference statements)
1
78
0
Order By: Relevance
“…Over the years, the relationship between morphology and ion conductivity has been investigated and more attention was devoted to polymers with ordered structures [14][15][16]. Different block copolymers, mostly AB diblocks, have been designed to control the morphology of the polymer membranes in order to improve proton conductivity [17,18,20,21]. Most AB block copolymers for fuel cell applications contain a hydrophobic block and a hydrophilic block.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the relationship between morphology and ion conductivity has been investigated and more attention was devoted to polymers with ordered structures [14][15][16]. Different block copolymers, mostly AB diblocks, have been designed to control the morphology of the polymer membranes in order to improve proton conductivity [17,18,20,21]. Most AB block copolymers for fuel cell applications contain a hydrophobic block and a hydrophilic block.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the formation of these composite structures resulted from the adsorption, combination, and selfassembly of P2VP molecules and inorganic species at the liquid/liquid interface. It is well known that block copolymers have more abundant assembly behaviors than homopolymers, which have been studied extensively in solutions and in thin layers deposited on solid substrates [15][16][17][18][19][20] and at the air/water interface [26]. We also noticed that a diblock copolymer, polystyrene-blockpoly(2-vinylpyridine) (PS-b-P2VP), could self-assemble into honeycomb structures doped with silver and gold nanoclusters at the liquid/liquid interface [27].…”
Section: Introductionmentioning
confidence: 90%
“…The former two kinds of methods are most commonly used. Recently, the self-assembly of polymers, especially block copolymers, has aroused an increasing research interest [15,16] due to their abundant self-assembly behaviors. The micellization and microphase separation of block copolymers in solutions and thin films have been utilized extensively to fabricate the organized composite structures of polymer/nanoparticles [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1 These composites not only have desirable properties, such as good processing ability, and mechanical and chemical stability, but also exhibit new optical and electronic properties resulting from cooperative interactions between the polymer molecules and nanoparticles. Various micro-and nanostructures have been observed in solutions, [13][14][15] thin lms, 15,16 and at the air/water interfaces 17,18 due to the micellization and microphase separation of the polymer molecules, and these include micelles, reverse micelles, vesicles, parallel and perpendicular cylinders, lamellar structures, ribbons, and 2D networks. Recently, the selfassembly of polymers, especially block copolymers, has attracted considerable attention due to the combination of polymer blocks containing different and unique properties.…”
Section: Introductionmentioning
confidence: 99%